Relationship between stress and development of entomopathogenic bacteria Pantoea (Erwinia) agglomerans (herbicola), and Bacillus cereus in several species of the white grub complex (Col: Melolonthidae) (Phyllophaga spp., Anomala spp. and Cyclocephala spp. - Vargas, Edgar (2016)
Concentrations of Colony Forming Units (CFU) were determined for two entomopathogenic bacteria (Pantoea agglomerans and Bacillus cereus), at the egg, larval, pupal, and adult stages of agriculturally important Phyllophaga and Cyclocephala white grubs, which were collected in five agroecosystems in Costa Rica. L2 and L3  larvae of Phyllophaga elenans collected in all regions where the study was conducted were extensive carriers of Pantoea agglomerans and Bacillus cereu. L2 and L3 larvae of Phyllophaga obsoleta, Phyllophaga menetriesi, Cyclocephala sanguinicollis and Cyclocephala castaniella found in the Central Valley and Central Pacific regions were carriers of Pantoea agglomerans and Bacillus cereus bacteria. In 60% to 90% of larvae in all white grub varieties studied, Pantoea agglomerans showed greater concentrations of CFU than Bacillus cereu, which showed the lowest CFU concentration. Egg, pupal, and adult mortality in all Phyllophaga species was due to Pantoea agglomerans in 62%, 80% and 22.5% of the cases, respectively. A possible antagonistic interaction between Pantoea agglomerans and Bacillus cereus is also discussed. In general, it was noted that light and larval manipulation were the main stress factors affecting these scarabids.